Вопрос от пользователя

1/2+(3m/1-3m+2m/3m+1)*9m2-6m+1/6m2+10m

Ответ редакции сайта ответик

1frac{1}{2} + ( frac{3m}{1-3m } +  frac{2m}{3m+1} ) *  frac{9m^2-6m +1}{6m^2+10m} =      =  frac{1}{2} +   frac{3m(3m+1) -2m (3m-1)}{-(3m-1)(3m+1)} *  frac{(3m-1)^2}{2m(3m+5)}  =      =  frac{3}{2} +  frac{9m^2+3m -6m^2+2m}{-(3m-1)(3m+1)} *  frac{(3m-1)^2}{2m(3m+5)} =     = frac{1}{2} +  frac{3m^2+5m }{- (3m-1)(3m+1)} *  frac{(3m-1)^2}{2(3m^2+5m)} =      = frac{3m+1}{2(3m+1)} -  frac{2(3m-1)}{3m+1 } =   =   frac{-3m+3}{2(3m+1)} =   1.5 *  frac{1-m}{3m+1}